4 - Oil Minorities and the Politics of Resource Control in Nigeria: DOI: 10.4314/ad.v30i4.22241 - Anugwom, Edlyne E. (Africa Development, 2005)
The paper examines the contentious nature of resource control and distribution in Nigeria. It avers that resource control has been a big problem confronting the Nigerian state from inception. This fact has not been helped by the heterogene ous nature of Nigeria, the weak capacity of the Nigerian state, the politics of resource allocation and the primordial bend of leadership. Therefore, the con testations over resources have been heightened in recent years by the politicisation and ethnicization of the resource allocation process by the Nigerian state and its elites. In this situation, the Niger Delta minority ethnic groups have seen them selves as victims of this politicisation of resource control by the dominant ma jority ethnic groups in control of state power. This allegation of marginalization in resource control is given further impetus by the decline of the derivation principle of revenue allocation, over centralization of the resource allocation process and the general socio-economic plight of the region in spite of being the source of the oil upon which Nigeria's monoeconomy has depended in the last three decades. Therefore, the grievance of the Niger Delta minorities and the general conflict and violence over resource control in Nigeria can only be mean ingfully addressed through a committed restructuring of the fiscal system